Fonem Segmental Bahasa Kadai - Fida Febriningsih (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
This is a descriptive qualitative research, which aims to identify the segmental phonemes in Kadai language. The result shows that the segmental phonemes of Kadai language consists of vowels: [a], [i], [u], [e], and [o]; consonants: [b], [c], [d], [f], [g], [h], [j], [k], [ l], [m], [n], [p], [r], [s], [t], [w], and [y]; two varieties of diphthong: up dipthong ([ai], [au], [oi], [ou], [ae], [ao], [eu], and [ei]) and down diphthong ([uo], [ua], [ue], [ia], [io], [ie], [ea], and [oa]); and it is also founded four varieties of vocabulary structure (two syllable, three syllable, four syllable, and five syllable).